Integrated Time Management System - Ahmad, Shahida (Universiti Teknologi Petronas, 2006)
The development of this project will focus on the Information and Communication Technology (ICT), and Business Information System (BIS) department regarding the lecturer attendance. The objective of this project is to study the current lecturer attendance process andto automate the process by developing the Pre-Integrated Time Management prototype. It is to ensure that the system satisfied the entire user which is lecturers, head programme and students; to eliminate the redundant stage in the current manual process and to make the business process faster and organize. The problem with the current process is there are no efficient ways to track lecturer attendance, keep attendance records, to notify the availability of the lecturer, to make an appointment as well as request and approve leave. Due to no efficient way to keep track and store lecturer attendance, it can lead to data redundancy and lost in the middle ofthe process. The methodology that selected for the system development is Iterative Model. For the data collection, a survey is conducted to get the students feedbacks through questionnaires and interviews. 'Integrated Time Management System' is developed to substitute the existing manual process to computerized system.